Notes on the geographic variation of Lopinga gerdae Nordström, 1934 Lepidoptera, Nymphalidae, Satyrinae) - Huang, Si-Yao; Lang, Song-Yun (Zootaxa, 2016)
Lopinga gerdae Nordström, 1934 (Satyrini) is a species geographically restricted to S. Gansu, Northwest China. It was described from four males and one female collected from “Ka-tien-kou” on 18.VII.[1930] and “Kung-tze-tagga im Tsaluk-Tal, Minshan” on 19.VII.[1930] by Dr. David Hummel (Nordström, 1934). Though exact sites could not be located, we were able to confirm that “Ka-tien-kou” and “Kung-tze-tagga” are two small places in a valley of Minshan Mts. in the southwestern part of the Jone [Choni in Nordström (1934)] County. In recent years, specimens of this species were collected from Tewo by Eckweiler (Görgner, 1990), from Xiahe by Bozano (Bozano, 1999), from Daban-shan by Floriani I., Floriani A. and Saldaitis A. (Bozano pers. comm.), and from Liupan-shan by Chinese researchers. Specimens from different localities having been compared and their distribution considered, it is found that this species varies continuously from west to east in its small range (Fig. 16), with the individuals collected around the type locality being the intermediate form. However, after dissecting the male genitalia, the result suggests that the populations from Xiahe and Liupan-shan should still be regarded as extreme forms of the same species.